Онтоморфогенез окремих видів роду Primula L. у культурі в умовах Північного Лісостепу України - Pereboichuk, O.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to study ontomorphogenesis and morphological features of the species of the genus Primula L. introduced in M.M. Gryshko National Botanical Garden of the NAS of Ukraine and interspecific hybrids of their own selection in connection with their great promise for ornamental horticulture of the Forest-Steppe of Ukraine. Material and methods. The material of research was seeds and plants of introduced species (P. denticulata Sm., P. saxatilis Kom., P. veris L., P. vulgaris Huds., P. woronowii Losinsk.) and interspecific hybrids of the own selection of the group P. pruhonicensis hybrids. The periodization of ontogenesis and the allocation of quality indicators to establish the age of the plants was carried out on the basis of morphological analysis in accordance with the methodological guidelines of I.P. Ignatieva and A.A. Uranov. The life forms of plants were determined according to the classification of I.G. Serebryakov and K. Raunkier. Morphological descriptions were carried out in accordance with the atlases of descriptive morphology of higher plants of Z.T. Artyushenko, M.E. Kirpichnikov and A.A. Fedorov. Results. The features of individual growth and development of five species and interspecific hybrids of their own selection in culture in the conditions of the northern Forest-Steppe of Ukraine are investigated. The mass of 1000 seeds, depending on the taxon, varies from 0.05 to 1.23 g, the similarity of seeds is 51.6–98.6 %. During the first year of vegetation, individuals pass through age states from the germ to virginal state. In the virgin state, plants overwinter and develop during the second year of the growing season. In the spring of the third year they reach the generative period. On the 6–8 years of the growing season, the first signs of dying off of the rhizome appear, the plants gradually pass into the postgeneration period. Conclusions. It has been established that P. denticulata, P. saxatilis, P. veris, P. vulgaris, P. woronowii, P. pruhonicensis, under culture conditions, has a full cycle, they set high-grade seeds. The viability of the seed depends on the biological characteristics of the species and its storage conditions. In the process of development from seed to generative individuals, plants pass through all age states and differ in morphological features, biometric parameters and rates of passage through the various stages of the life cycle. Indicator signs of age conditions are: for germ – cotyledons, tap and lateral roots; for juvenile individuals – juvenile leaves, an additional roots; for immature – leaves are similar in shape to adult plants, winged petiole, epiogenic rhizome, and fibrous root system; for virginal individuals, the leaves are characteristic of adult plants; lateral buds of regeneration. The ontogeny of life forms of plants varies: the germ – with tap roots monopodial with the growth of the shoot, juvenile and immature individuals – mixed root system with monopodial growth rhizome, virginal – clustering-shaped root with monopodial or sympodial growth of rhizome, generative individuals – short-rhizome herbaceous perennials.